Strategic Capabilities And Export Performance Of Manufacturing Smes In Malaysia: The Impacts Of Individual, Firm And Industry Level Factors - Tuah, Siti Normah Awang (2018)
Research on export performance among SMEs in Malaysia has become more significant nowadays as export is a major source of income for most countries. It is important for SMEs especially those in emerging countries like Malaysia to look into and put their efforts to strategize their capabilities to respond to the global competition and business opportunities in enhancing their export performance. Specifically, the study attempts to examine the impacts of individual level factor, firm level factors and industrial level factors towards strategic capabilities in enhancing the export performance. While considering strategic capabilities as having significant impact on export performance, this study also examines the role of government export assistance as moderator whether it strengthening the relationship between strategic capabilities and export performance. Drawing upon the combination of Resource-Based View Theory (RBV), Dynamic Capability Theory and Internationalization Theory, a conceptual framework is developed for further investigation. A quantitative approach was employed in this study and a total of 187 responses from SME exporters were received and further analyzed using Partial Least Squares (PLS) technique. The results demonstrated that; Export-Market Oriented (EMO) has no significant impact on strategic capabilities, while intellectual capital and environmental conditions partially have positive and significant impacts on some elements of strategic capabilities. Strategic capabilities in terms of innovation and technology have positive and significant impacts on export performance and government export assistance in the form of access to financing strengthens the relationship between strategic capabilities (marketing capability and innovation capability) and export performance. The findings also provide invaluable implications to both theory and practice.